Evaluation of the threshold values for the propagation of a fatigue crack starting at a V-notch - Klusák, Jan; Knésl, Zdeněk (Computer Assisted Methods in Engineering and Science, 2002)
This paper presents a simple method for evaluating the threshold value for fatigue cracks that emanate from a V-notch. The proposed method is based on the similarities between the elastic-stress fields around the tip of a crack and the tip of a V-notch. Threshold values for fatigue cracks that emanate from a V-notch are expressed by means of the threshold value for the propagation of a high-cycle-fatigue crack and the opening angle of the V-notch. The corresponding calculations were performed by the finite-element method.